Rejoinder: Moving the Management Field Forward. (October 2015) - Walsh, Isabelle; Holton, Judith A.; Bailyn, Lotte; Fernandez, Walter; Levina, Natalia; Glaser, Barney
It has become essential and urgent that significant actors in the management field of research become aware of the current rejection of previously accepted philosophical caricatures. The unrealistic though "tidy" paradigmatic dichotomy, positivism/quantitative/deduction versus interpretivism/qualitative/induction, is being rejected. Instead, a growing and "untidy" consensus is emerging that helps to position grounded theory (GT) in the research landscape. This growing consensus includes perspectives that range from nomothetic to idiographic and highlights data-driven exploratory approaches in opposition to theory-driven confirmatory approaches. While the foundational pillars of GT (emergence, theoretical sampling, and constant comparison) have to be respected when conducting a GT study, there certainly is plenty of room for creativity in the implementation of a data-driven exploratory GT approach. GT is not limited to an all-encompassing method for qualitative or interpretive research: It is much broader and may be applied from various philosophical perspectives that range from nomothetic to idiographic.